Understanding the Effect of Different Abiotic Stresses on Wild Marigold (Tagetes minuta L.) and Role of Breeding Strategies for Developing Tolerant Lines - Kumar, Ajay; Gautam, Rahul Dev; Kumar, Ashok; Singh, Satbeer; Singh, Sanatsujat (Frontiers in Plant Science, 2022)
Wild marigold has a growing demand for its essential oil in the flavor and fragrance industries. It can be grown over a broad range of climates, but the changing climatic conditions lead to abiotic stresses thus restricting its productivity. Abiotic stresses at elevated levels result in the reduction of germination, growth, and essential oil quality of wild marigold leading to heterogeneous and inferior grades of ‘Tagetes oil.' Drought, salinity and heavy metal stress at elevated levels have common effect in terms of ROS formation which are the major cause of growth deterioration in wild marigold. Temperatures above 35°C inhibit the seed germination. Irradiance stress reduces the biomass and essential oil yield. Waterlogging adversely affects the survival of wild marigold in high rainfall regions. Application of plant nutrients (fertilizers) modulates the biomass and essential oil yield. Wild marigold employs multiple tolerance mechanisms to cope up with the adverse effects of abiotic stresses such as increased activity of antioxidants to maintain cellular redox homeostasis, enhanced lipid peroxidation in cell membrane to maintain cell wall architecture, production of secondary metabolites and accumulation of osmolytes. In this review we tried to understand how abiotic stresses affect wild marigold. Understanding of the physiological changes and biochemical characteristics of stress tolerance will contribute to the development of stress tolerant lines of wild marigold.